Analisis Faktor-Faktor Yang Mempengaruhi Penetapan Target Penerimaan Pajak Reklame Di Kota Bandung - Rusita Pratama; Iyeh Supriatna (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
One of the efforts made by the City Government of Bandung in maximizing Regional Original Income is by optimizing local tax revenue, especially the billboard tax. In Bandung, the advertisement tax revenue is still far from the target set because there are many unlicensed or illegal billboards that cannot be taxed. The purpose of this study was to analyze the effect of population, industry, and per capita income on advertising tax revenue targeting. This type of research is quantitative research. Sources of data used in this study are secondary data. The method used in this study is Multiple Linear Regression Analysis and analyzed using the SPSS version 26 software program. The results of this study indicate that the population, number of industries and income per capita are not proven to have a positive effect on the target setting of advertisement tax revenue.